2009
DOI: 10.3921/joptom.2009.138
|View full text |Cite
|
Sign up to set email alerts
|

Results of Cataract Surgery in the Very Elderly Population

Abstract: PURPOSE:The aim of this study was to retrospectively evaluate the effect of cataract surgery on visual acuity (VA) and daily living activities in participants aged over 80 years. METHODS: For eighty-three eyes from eighty three eligible patients aged 80 or above who had undergone cataract surgery between 2000 and 2005, preoperative and postoperative best-corrected visual acuity (BCVA), satisfaction score for daily living activities, surgical complications, and retinal pathologies affecting vision were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…Three studies showed that approximately 70% of very elderly adults achieved improvement in visual acuity. [9][10][11] One study demonstrated that visual acuity improved in 94% of individuals aged 90 and older. 12 The difference could be attributed to the prevalence of systemic and ocular comorbidities, variation in sample size, and duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies showed that approximately 70% of very elderly adults achieved improvement in visual acuity. [9][10][11] One study demonstrated that visual acuity improved in 94% of individuals aged 90 and older. 12 The difference could be attributed to the prevalence of systemic and ocular comorbidities, variation in sample size, and duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Three previous studies reported that approximately 70% of very elderly adults could achieve improvement in visual acuity after cataract surgery. [9][10][11] Small sample size or short duration of follow-up constrained these studies. Larger sample size and longer duration of follow-up will provide a clearer picture of the clinical outcomes in this group of individuals.…”
mentioning
confidence: 99%
“…The same finding was reported by Mahmoud &Monsudi (2012), on the impact of cataract surgery on visual function and quality of life of elderly patients in Birnin Kebbi, Nigeria; who found that the mean age was 61.6±9.8 years (36) . Moreover, a studies conducted by Leon et al (2008) and Mehmeta & Abuzer (2009) on the impact of cataract surgery on visual acuity and quality of life of elderly people , who reported that the mean age was 74.32±6.44, 86.80±5.24 years respectively (30,31) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on cataract surgery outcomes in the elderly population (>85 or >90 years) have been reported in Japan [1], Sweden [2,4], UK [5][6][7], Denmark [8], Germany [9], Korea [10], USA [11][12][13], China [14], Turkey [15], and Israel [16]. However, none of these studies included a matched control in systemic and ocular comorbidity, which may confound the age effect [17].…”
Section: Introductionmentioning
confidence: 99%